The problem of the freedom of will: historico-philosophical topics in the analytic perspective. Hausmannn, M., & Noller, J. (Eds.). (2021). Free Will. Historical and Analytic Perspectives. Cham: Springer; Palgrave Macmillan. - Sepetyi, Dmytro (Sententiae, 2022)
Rewiew of Hausmannn, M., & Noller, J. (Eds.). (2021). Free Will. Historical and Analytic Perspectives. Cham: Springer; Palgrave Macmillan.